2020
DOI: 10.12707/riv19096
|View full text |Cite
|
Sign up to set email alerts
|

Sofrimento nos enfermeiros em cuidados de saúde primários

Abstract: Resumo Enquadramento: O sofrimento nos enfermeiros advém da prestação de cuidados ao doente em sofrimento e de fatores relacionados com as condições de trabalho. É uma experiência multidimensional que ocorre em situações de perda, dano ou ameaça à integridade da pessoa. Objetivo: Comparar as médias das dimensões do sofrimento (Dor Emocional, Perda Relacional e Evitamento) em função das variáveis sociodemográficas e profissionais dos enfermeiros. Metodologia: Estudo descritivo e transversal de natureza quantita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
1
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 12 publications
1
1
0
3
Order By: Relevance
“…Pires et al (2020) found a similar reality in a study with nursing professionals where they found a prevalence of the female gender and a predominance of nursing technicians over nurses. Concerning the prevalence of the female gender,Santos et al (2017) explain that, despite the changes occurring in this scenario, feminization is still a strong characteristic among healthcare professionals, given that more than 90% of job vacancies are filled by women.…”
supporting
confidence: 52%
See 1 more Smart Citation
“…Pires et al (2020) found a similar reality in a study with nursing professionals where they found a prevalence of the female gender and a predominance of nursing technicians over nurses. Concerning the prevalence of the female gender,Santos et al (2017) explain that, despite the changes occurring in this scenario, feminization is still a strong characteristic among healthcare professionals, given that more than 90% of job vacancies are filled by women.…”
supporting
confidence: 52%
“…These professionals have different workloads, being exposed to different occupational risks (Freire & Costa, 2016). Thus, the specificities of workloads and organizational factors to which nurses and nursing technicians are exposed can impact their physical and/or mental health (Souza et al, 2017;Cargnin, Schneider, Vargas, & Machado, 2019;Pires et al, 2020). Besides the occupational factors, the socioeconomic conditions can also be related to the presence of pain, interfering in the quality of life of these professionals (Ribeiro et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Se ha concebido el sufrimiento de los enfermeros como una experiencia multidimensional que se deriva de la prestación misma del servicio, su relación con los pacientes, así como de las condiciones del trabajo. Esta experiencia podría verse intensificada en situaciones de pérdida, daño o amenaza a la integridad del profesional (9). Así mismo, se ha afirmado que para este personal se produjo intensificación de las tareas, demandas de resultados positivos, expectativa social, no poder realizar plenamente sus relaciones personales y precarización de las condiciones de trabajo (6).…”
Section: Introductionunclassified
“…De acordo com estas conceptualizações do sofrimento, seria espectável que esta componente inerente à actividade profissional do enfermeiro Da revisão de literatura percebe-se que face à exposição e ao acompanhamento do sofrimento de quem se cuida leva a graus mais acentuados de sofrimento naquele que cuida/cuidou de uma pessoa com doença ou problema de saúde (Pires, Monteiro, & Vasconcelos-Raposo, 2020). Não basta afirmar que os cuidadores são uns heróis invisíveis e solitários, pois nem sempre são vistos como fundamentais ou valorizados como cuidadores, quer seja pela família, quer pelos serviços de saúde (Luzardo & Waldman, 2004).…”
Section: Introductionunclassified
“…Em Portugal (Pires et al, 2020;Schaefer, 2017) a maioria das investigações sobre o sofrimento tem-se focado no estudo do sofrimento de doentes ou cuidadores informais, descurando os profissionais de saúde, nomeadamente os enfermeiros que diariamente se deparam com o sofrimento e até perda de vida daqueles de quem cuidam, pelo que com este trabalho procuramos colmatar, em parte, esta lacuna.…”
Section: Introductionunclassified